Konstruksi Prinsip Kinerja Public Relations Dalam Pandangan Syariat Islam - Mubarok, Mubarok; Marhaeni K, Dian (Universitas Semarang, 2016)
PR performance principle formulated as part of the management functions to achieve the objectives of an organization. Likewise with the influence of religious scriptures embraced by every individual involved in the communication process. One scripture that the reference human life is the Qur'an as a way of life of Muslims. Related to the practice and science of public relations it is interesting to look at dikontruksi how Islamic law principle of PR performance. The scales of the Shari'a as an integral part of the life of a Muslim will guide how he practice the principles of PR performance. Institutions are trying to get support through activities that can provoke support from the public without coercion or through a stage of conflict. Arthur W. Page mentions a number of principles that can be used in practice and as a philosophical PR in maintaining relations with the public institutions.